3D‐Printed Poly(acrylic acid–vinylimidazole) Ionic Polymer Metal Composite Actuators. Issue 1 (26th October 2022) - Wang, Yuyang; Liang, Yue; Bansode, Archana; Lou, Xiaoyuan; Zhang, Xinyu; Beckingham, Bryan S.; Auad, Maria L.
Abstract: Ionic polymer–metal composites (IPMC)—constructed using an ionic polymer sandwiched between metal electrodes—have shown great potential for the fabrication of soft actuators. IPMC architectures have many advantages including low actuation voltage, fast response, basic control, and relatively light weight. Poly(acrylic acid) (PAA)‐based ion exchange membranes are of particular interest for IPMC devices due to their large ion exchange capacity and ease of preparation; however, they suffer from relatively weak mechanical strength. Here, PAA‐based soft actuators are synthesized with enhanced mechanical properties and proton conductivity through the incorporation of hydrogen bonding interactions with imidazolium groups via copolymerization with 1‐vinylimidazole. In addition to examining the impact of composition on physiochemical (swelling, glass transition, decomposition, Young's modulus, etc.) and electrochemical (specific capacitance) properties, an additive manufacturing process, digital light projection (DLP), is utilized to fabricate complex geometries demonstrating the potential for the fabrication of IPMC devices with complex actuation modalities. Planar DLP 3D‐printed IPMC actuators of varied polymer compositions are fabricated with activated carbon and copper electrodes, and their actuation performance is evaluated in air, where large bending deformation is observed (14°–37°). Abstract : 3D printing of polymers for ionic‐polymer‐metal composite(IPMC) actuators enables fabrication of complex actuator structures but requires development and optimization of 3D printable ionic polymers. Here, digital light projection 3D printed poly(acrylic acid‐ co ‐vinylimidazole) of varied composition incorporating both physical crosslinks and a hydrogen bonding network is investigated and the bending performance of fabricated IPMC actuators is evaluated. .